Stacked Difference-in-Differences - Wing, Coady,Freedman, Seth,Hollingsworth, Alex (National Bureau of Economic Research, 2024)
This paper introduces the concept of a
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Differenz von Differenzen; Kausalanalyse; Schätztheorie; Ökonometrie; Econometrics; Estimation: General; General